1965
DOI: 10.1080/00021369.1965.10858513
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Terpenes by the Condensation of Aliphatic Compounds

Abstract: The condensation of mesityloxide with 4-diethylaminobutanone-(2) in the presence of potassium t-butoxide gave the products containing piperitenone together with isoxylitones, which were identified by gas chromatography and chemical methods. The effects of the combination of condensing agent, solvent, molar ratio of reagents and reaction temperature on the components in the condensation products were studied. It was found that piperitenone was able to obtain in an yield of 51% on the basis of 4-diethylaminobuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One of the authors has prepared 1 successfully with a 51% yield by the condensation of 2 with 3 or 4-diethylamino-2-butanone using Triton B in ether followed by removal of isoxylitones by the formation of their semicarbazones 6 ) We have also confirmed the structures of isoxylitone-A and B, the main components of isoxylitones, to be 4E and 4Z. 7 ) In these investigations, we have found that when alkali metal alkoxide was used as condensing agent the self-condensation of 2 occurred in an aprotic solvent (e.g., n-hexane, benzene), but little or no reaction occurred if the solvent was replaced by a protic solvent [e.g., ethanol], tetrahydrofuran (THF) or a hydrous aprotic solvent.…”
mentioning
confidence: 99%
“…One of the authors has prepared 1 successfully with a 51% yield by the condensation of 2 with 3 or 4-diethylamino-2-butanone using Triton B in ether followed by removal of isoxylitones by the formation of their semicarbazones 6 ) We have also confirmed the structures of isoxylitone-A and B, the main components of isoxylitones, to be 4E and 4Z. 7 ) In these investigations, we have found that when alkali metal alkoxide was used as condensing agent the self-condensation of 2 occurred in an aprotic solvent (e.g., n-hexane, benzene), but little or no reaction occurred if the solvent was replaced by a protic solvent [e.g., ethanol], tetrahydrofuran (THF) or a hydrous aprotic solvent.…”
mentioning
confidence: 99%